Math, asked by mnewfuture, 1 year ago

Find the solution for the following equation under the initial value of y (pi/2)=1 . y' – 2xy = e^(x^2)cos³ x

Answers

Answered by Swarup1998
0

To solve. \mathrm{y'-2xy=e^{x^{2}}cos^{3}x}

Given. \mathrm{y\left(\frac{\pi}{2}\right)=1}

Solution.

Now, \mathrm{y'-2xy=e^{x^{2}}cos^{3}x}

\Rightarrow\mathrm{\frac{dy}{dx}-2xy=e^{x^{2}}cos^{3}x\quad...(1)}

Then, \mathrm{I.F.=e^{\int (-2x)dx}=e^{-x^{2}}}

Multiplying \mathrm{(1)} by \mathrm{I.F.=e^{-x^{2}}}, we get:

\quad \mathrm{\frac{d}{dx}\left(e^{-x^{2}}y\right)=cos^{3}x}

\Rightarrow \mathrm{d\left(e^{-x^{2}}y\right)=cos^{3}x\:dx}

\Rightarrow \mathrm{d\left(e^{-x^{2}}y\right)=\frac{1}{4}cos3x\:dx+\frac{3}{4}cosx\:dx}

On integration, we get:

\quad \mathrm{\int d\left(e^{-x^{2}}y\right)=\frac{1}{4}\int cos3x\:dx+\frac{3}{4}\int cosx\:dx}

\Rightarrow \mathrm{e^{-x^{2}}y=\frac{1}{12}sin3x+\frac{3}{4}sinx+C\quad...(2)}

where \mathrm{C} is constant of integration

When \mathrm{y\left(\frac{\pi}{2}\right)=1}, we get:

\quad \mathrm{e^{-\frac{{\pi}^{2}}{4}}=-\frac{1}{12}+\frac{3}{4}+C}

\Rightarrow \mathrm{C=e^{-\frac{{\pi}^{2}}{4}}-\frac{2}{3}}

Putting \mathrm{C=e^{-\frac{{\pi}^{2}}{4}}-\frac{2}{3}} in \mathrm{(2)}:

\quad \mathrm{e^{-x^{2}}y=\frac{1}{12}sin3x+\frac{3}{4}sinx+e^{-\frac{{\pi}^{2}}{4}}-\frac{2}{3}}

This is the required solution.

Similar questions